Phytoagent Deoxyelephantopin and Its Derivative Inhibit Triple Negative Breast Cancer Cell Activity through ROS-Mediated Exosomal Activity and Protein Functions - Shiau, Jeng-Yuan; Chang, Yong-Qun; Nakagawa-Goto, Kyoko; Lee, Kuo-Hsiung; Shyur, Lie-Fen (Frontiers in Pharmacology, 2017)
A novel plant sesquiterpene lactone derivative, DETD-35, originating from parental deoxyelephantopin (DET) was previously observed to effectively suppress human triple negative breast cancer (TNBC) MDA-MB-231 cell activity and tumor growth in mice. In this study, the mechanisms underlying the activity of DETD-35 were elucidated. DET and DETD-35 induced reactive oxygen species (ROS) which caused structural damage and dysfunction of mitochondria and increased cytosolic calcium level, subsequently evoking exosome release from the cancer cells. Intriguingly, exosomes induced by both compounds had an atypical function. Cancer cell-derived exosomes commonly show metastatic potential, but upon DET/DETD-35 treatment exosomes showed anti-proliferative activity against MDA-MB-231 cells. Quantitative proteome analysis of TNBC cell-secreted exosomes showed that DET and DETD-35 attenuated the expression of proteins related to cell migration, cell adhesion, and angiogenesis. Furthermore, several exosomal proteins participating in biological mechanisms such as oxidative stress and decrease of transmembrane potential of mitochondria were found deregulated by treatment with either compound. Pretreatment with ROS scavenger, N-acetylcysteine, blockaded DET- or DETD-35-induced oxidative stress and calcium dependent exosome release mechanisms, and also reverted DET- or DETD-35-induced reprogramming exosomal protein expression profiles resulting in attenuation of exosomal toxicity against TNBC cell proliferation. In summary, this study shows that a plant-derived sesquiterpene lactone DET and its analog DETD-35 inhibitory TNBC cell activities through oxidative stress-induced cancer cell releasing exosomes in tandem with alteration of exosomal protein composition and functions. The findings of this study suggest that DETD-35 may be suitable for further development into an anti-TNBC drug.